A 5T1C pixel circuit compensating mobility and threshold voltage variation. (November 2021) - Zeng, Yongtao; Chu, Hongzhen; Wei, Ning; Li, Yuehua; Wang, Xinlin; He, Hongyu
Abstract: A pixel circuit is presented for active-matrix organic light-emitting diode (AMOLED) displays. The circuit contains five thin-film transistors (TFTs) and one capacitor (5T1C). In the circuit, by decreasing the driving TFT's source voltage, the mobility-related discharge voltage is obtained. By inputting the data voltage in the programming stage, the circuit can compensate both threshold voltage variation and mobility variation using only one capacitor. Meanwhile, the circuit can prevent the current from flowing into the OLED when the OLED is not operated in the emission stage to prevent the image flicker. The circuit simulation results show that the OLED current error rate is lower than 5.7% when the threshold voltage varies ± 0 . 5 V, the error rate is lower than 5.5% when the mobility varies ± 30 % and the data voltage is above 0 V .